Mesh adaptation for time dependent simulation, optimization and control - Mohammadi, Bijan; Hecht, Frédéric (European Journal of Computational Mechanics, 2001)
The paper describes our adaptative design and control platform for aerodynamic configurations. The aim is to analyze the impact of mesh discretization and connectivity changes on the convergence of minimization algorithms applied to shape design and state control. Hence, we are interested in analyzing the impact of these changes for unsteady configuration simulations. We propose a transient fixed point approach for the set mesh-solution-gradient limiting these effects.